PENGARUH PENDAPATAN ASLI DAERAH, DANA PERIMBANGAN, DAN PERTUMBUHAN EKONOMI TERHADAP KEMISKINAN DI D.I. YOGYAKARTA - Noermanisa, Thania (Journal of Development Economic and Social Studies, 2023)
Poverty is a multidimensional and complex problem. The Special Region of Yogyakarta is one of the provinces in Java Island which has the worst poverty rate amongst the Java Island. Poverty can be reduced through economic growth and the implementation of fiscal decentralization. Therefore, this study aims to see the effect of Local Own-source Revenue (PAD), Balancing Funds, and Economic Growth on Poverty in the Special Region of Yogyakarta taken in the period of 2012 – 2021. The data were examined using panel data regression. Based on the regression results, Local Own-source Revenue and Balancing Funds are found to have a negative and significant impact on poverty, while Economic Growth is found to have a positive and insignificant impact on poverty. Overall, these three variables are significant to poverty with the measurement of R2 value for 0.8072 or 80.72%.